2012
DOI: 10.1073/pnas.1208110109
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual convergence of multi-component mixtures in olfaction implies an olfactory white

Abstract: In vision, two mixtures, each containing an independent set of many different wavelengths, may produce a common color percept termed "white." In audition, two mixtures, each containing an independent set of many different frequencies, may produce a common perceptual hum termed "white noise." Visual and auditory whites emerge upon two conditions: when the mixture components span stimulus space, and when they are of equal intensity. We hypothesized that if we apply these same conditions to odorant mixtures, "whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 32 publications
5
130
0
4
Order By: Relevance
“…In each of five trials, subjects activated three scratch-and-sniff microencapsulated odorant stickers (1 square inch), two containing an identical mixture of 20 components, and one containing a different yet perceptually similar mixture of 20 components (these odorant mixtures were different versions of olfactory white as in Ref. [34]). Order of odorants was counter-balanced.…”
Section: Experiments 3: Field Olfactory Discrimination Taskmentioning
confidence: 99%
“…In each of five trials, subjects activated three scratch-and-sniff microencapsulated odorant stickers (1 square inch), two containing an identical mixture of 20 components, and one containing a different yet perceptually similar mixture of 20 components (these odorant mixtures were different versions of olfactory white as in Ref. [34]). Order of odorants was counter-balanced.…”
Section: Experiments 3: Field Olfactory Discrimination Taskmentioning
confidence: 99%
“…5A). Experimental studies report similar numbers, e.g., s max ≈ 15 (36) and s max < 30 (6). However, Fig.…”
Section: Optimal Receptormentioning
confidence: 89%
“…For example, humans have about 300 distinct olfactory receptors (4), which can sense at least 2,100 odorant molecules (5), and the real number might be much larger (1). Moreover, humans can differentiate between mixtures of up to 30 odorants (6). Such remarkable molecular discrimination is thought to use a combinatorial code (7,8), where typical odorant molecules bind to receptors of multiple types (1,3).…”
mentioning
confidence: 99%
“…We are not aware, of any test of olfactory STM so far that has controled for sensory differences in the training set (cf. Weiss et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Such compositionality in olfaction would open commercial applications such as in the perfume industry or in smellies, films with accompanying olfactory stimuli. As one of the few to demonstrate this compositionality principle, Weiss et al (2012) found that olfactory white can be produced from the composition of around thirty odorants that spanned the perceptual space.…”
Section: Perceptionmentioning
confidence: 99%